Liraglutide; A New Hope for Obese Diabetics - Kumar, Ajeet; Kumar, Dileep; Razzaque, Salma; Kumar, Ashok; Kumar, Rajesh; Ghauri, Muhammad Ishaq; Yaseen, Mahjabeen (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To assess the effectiveness of liraglutide in reducing weight and Glycated haemoglobin (HbA1c) in type 2 diabetic patients. METHODOLOGY: This analytical observational study was conducted at Jinnah medical college hospital Karachi Pakistan. The Convenient sample technique was used for sample collection. Data was collected from January 2018 to April 2019, comprising of 68 patients receiving liraglutide therapy. They were analysed for changes in body weight and HbA1c after 12 and 24 weeks of liraglutide therapy. RESULT: In patients receiving oral anti-diabetics and liraglutide there was significant reduction in weight at 12 and 24 weeks, while with liraglutide alone weight and HbA1c was reduced at 12 weeks but no further reduction at 24 weeks, same effect was observed in insulin and liraglutide therapy, but in patient receiving insulin, liraglutide and metformin changes were sustained at 24 weeks. CONCLUSION: Liraglutide is effective therapy for controlling weight and HbA1c especially when given in combination with oral anti-diabetics and insulin. Key words: Diabetes mellitus, Obesity, Incretins, Liraglutide, Glucagon like peptides.